A Systematic Review and narrative synthesis of the methods used to teach adult airway management skills to novices - Grunewald, Kevin (Department of Anaesthesia and Perioperative Medicine, 2022)
Background: Airway management is an essential skill for healthcare providers across many disciplines. Inadequate airway management leads to adverse events and deaths. Clear guidance on the use of evidence-based educational methods to train novice airway managers is limited. Best evidence suggests using a “deliberate practice for mastery learning” approach to produce expertise in complex skills. Objectives: Our primary outcome is a narrative synthesis of the evidence evaluating instructional design elements employed to train novices in airway management. Our secondary outcome is a description of how these techniques employ deliberate practice principles. These data will inform recommendations for future airway training. Methods: We conducted a systematic review of English language studies published by June 2019. Studies evaluating educational interventions to improve airway management by novices were included. Studies were excluded if they only reported learner reactions to training (Kirkpatrick Level 1 outcomes). Data extraction was performed in duplicate using a standardised form and critical appraisal of the included studies was performed using a tool developed by Hawker, et al. Due to the heterogeneity of the data and in order to best highlight important themes, we performed a narrative synthesis of included studies. Further, we explicitly reviewed the studies using a deliberate practice lens to extract features consistent with this framework. Results: Our search yielded 506 studies of which 42 were eligible for inclusion. Most studies were rated poor quality and used small convenience samples. Studies included participants from a range of disciplines who were trained using multiple different interventions on part-task trainers, manikins and real patients. Most studies (60%) used overall intubation success rate as the primary outcome measure with only 21% of studies reporting first-pass success rate. Only 10% of studies explicitly mentioned deliberate practice. Important emerging themes include using checklists as scaffolding for progression, using video laryngoscopy to augment teaching, and using different manikins to mimic variations in human anatomy. Conclusions: Reported studies evaluating airway training are of poor quality. However, available evidence offers usable instructional design elements associated with durable learning and improved expertise. We have made suggestions for incorporating deliberate practice into future airway training. A commitment to evidence-based educational design could improve expertise in this critical skill. (Prospero registration: CRD42017077843)